Temperature changes in the function of the shape inherent to the band of exciton absorption in nanofilm of layered semiconductor - Derevyanchuk, A.V.; Pugantseva, O.V.; Kramar, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Represented in this paper is the method and results of theoretical
investigations aimed at the influence of spatial confinement effects, self-polarization of
heterojunction planes as well as exciton-phonon interaction on the position and shape of
the band corresponding to exciton absorption in nanofilms of layered semiconductor in a
dielectric matrix. The heterojunction is considered as unloaded, the nanosystem is
modeled by an infinitely deep quantum well and characterized by an essential difference
between dielectric permittivities on both sides of the heterojunction. Calculated in this
work are the dependences for the form-function of the absorption band on the thickness
of lead iodide nanofilm embedded into polymer E-MAA or glass, and on its temperature.
The results of calculations are in good accordance with known data of experimental
measurements.